2021
DOI: 10.25248/reas.e7826.2021
|View full text |Cite
|
Sign up to set email alerts
|

Effects of omega-3 supplementation on endothelial dysfunction in humans: a systematic review

Abstract: Objective: To evaluate the effects of omega-3 supplementation on endothelial dysfunction in humans, considering the lipid profile, inflammatory and oxidative stress markers. Methods: The search for the articles was carried out on the bases PubMed, Scopus, Cochrane and Web of Science, following the recommendations for Systematic Reviews and Meta-analysis of PRISMA. This study was registered in the International Prospective Register of Systematic Reviews database. After the process of searching and applying the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Nunzio and Bordini [ 18 ] verified the differences between polyunsaturated fatty acids in human hepatoma cells and observed that cells supplemented with DHA obtained a better antioxidant defense with SOD, GSH and GPx markers than those supplemented with EPA. However, it is still necessary to understand the effects of these nutrients in pathological conditions such as dyslipidemia [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nunzio and Bordini [ 18 ] verified the differences between polyunsaturated fatty acids in human hepatoma cells and observed that cells supplemented with DHA obtained a better antioxidant defense with SOD, GSH and GPx markers than those supplemented with EPA. However, it is still necessary to understand the effects of these nutrients in pathological conditions such as dyslipidemia [ 19 ].…”
Section: Discussionmentioning
confidence: 99%